COMPUTER CRIME - Ristyawati Ristyawati (JAKSTIK Journal, 2005)
Computer crime can be categorized as crimes of "White Colar Crime", which operates inmore use of the mind or brain. Definition of Cyber crime is any act that harm others orcertain parties who performed on digital media or with the aid of digital devices.